THE ROLE OF INDUSTRIAL ENTERPRISES IN THE DEVELOPMENT OF THE NATIONAL ECONOMY - Kamolov Abduraxmon (Galaxy International Interdisciplinary Research Journal, 2021)
This article considers some issues such as the socio-economic nature of the innovative potential of industrial enterprises, its components, the main factors in the formation and development of innovative potential.